2019
DOI: 10.1177/1060028019872940
|View full text |Cite
|
Sign up to set email alerts
|

Opioid and Benzodiazepine Requirements in Obese Adult Patients Receiving Extracorporeal Membrane Oxygenation

Abstract: Background: The use of extracorporeal membrane oxygenation (ECMO) sometimes requires deep levels of sedation (Richmond Agitation Sedation Scale [RASS] −5) in patients with acute respiratory distress syndrome (ARDS). The role of obesity in opioid and sedative requirements remains unclear in patients receiving ECMO. Objective: This study sought to determine whether obesity increases midazolam and opioid requirements in patients receiving venovenous (vv)-ECMO up to the first 7 days after initiation. Methods: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…23 In a retrospective cohort study of 81 (38 obese and 43 nonobese) patients receiving VV-ECMO, 31 (38%) required a switch to hydromorphone within the first 7 days. 23…”
Section: Analgosedation Medicationsmentioning
confidence: 99%
“…23 In a retrospective cohort study of 81 (38 obese and 43 nonobese) patients receiving VV-ECMO, 31 (38%) required a switch to hydromorphone within the first 7 days. 23…”
Section: Analgosedation Medicationsmentioning
confidence: 99%
“…Al-Soufi reported no mortality difference according to weight quartiles in 1,334 adults in an earlier ELSO registry analysis, though a trend toward decreased mortality was noted among the highest quartile [ 18 ]. Small case series found no survival difference with BMI dichotomized at 30 kg/m 2 [ 19 ], 35 kg/m 2 [ 20 ], or 40 kg/m 2 [ 11 ], as a continuous variable [ 8 , 9 , 35 ] or stratified by subcategories [ 9 , 10 , 12 ], although a trend toward improved survival was suggested for the highest BMI values [ 11 , 12 ]. A systematic review and meta-analysis of mixed cardiac and respiratory ECMO patients found no association of BMI ≥ 30 kg/m 2 with mortality [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…21 Although increased fentanyl requirements in an obese ECMO population have not been well established, the theoretical risk still remains. 22 Because upward of 50% of COVID-19 patients on VV-ECMO fall into an obese category, this risk should be taken into consideration with prolonged used of fentanyl in the COVID-19 VV-ECMO population. 9,10 Furthermore, tachyphylaxis with prolonged opioid use in critically ill patients is a common reason for requiring transition to another agent, and opioid rotation for these patients adds to the armamentarium of strategies to address concerns of tolerance.…”
Section: Parenteral Opioidsmentioning
confidence: 99%
“…43 Despite its significant lipophilicity, there were no observed differences in midazolam requirements when stratified by obesity. 22 There is a paucity of data evaluating other benzodiazepines for sedation management in ECMO. In vitro data suggest that out of the benzodiazepines, lorazepam undergoes the least amount of adsorption to circuitry and overall drug loss; however, the extent of drug loss even with lorazepam is still substantial.…”
Section: Parenteral Benzodiazepinesmentioning
confidence: 99%